2015
DOI: 10.4037/ajcc2015500
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Systems for Outcome Prediction in a Cardiac Surgical Intensive Care Unit: A Comparative Study

Abstract: A closed-book, multiple-choice examination following this article tests your under standing of the following objectives:1. Compare and contrast 5 scoring systems and their ability to predict morbidity and mortality in the cardiac patient population. 2. Identify preoperative, intraoperative, and postoperative variables when using a prospective study. 3. Describe the performance of each scoring system. Methods Consecutive patients admitted to a cardiac surgical intensive care unit (CSICU) were prospectively stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
1
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 28 publications
(31 reference statements)
3
25
1
11
Order By: Relevance
“…(16) Exarchopoulos et al noted that SOFA score is one of the most significant predictors of mortality and in-hospital postoperative comorbidities in cardiac surgery patients. (17) …”
Section: Discussionmentioning
confidence: 99%
“…(16) Exarchopoulos et al noted that SOFA score is one of the most significant predictors of mortality and in-hospital postoperative comorbidities in cardiac surgery patients. (17) …”
Section: Discussionmentioning
confidence: 99%
“…This chain reaction results in tissue perfusion defects, which eventually causes an increase in the mortality predicting score (APACHE-II) in an ICU setting. A previous study showed that APACHE-II scoring system is effective for predicting the mortality at an early period (23) . Furthermore, a study consisting of 523 cases, which was performed to detect ICU mortality, reported the usefulness of APACHE-II scoring system (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The overall 30-day mortality was 10.3% which is considered to be higher than the average mortality reported in previous studies 9.3%, 9.6% and 6%. [11][12][13] This may be due to the higher rate of postoperative cardiac and respiratory 14 Many studies have been conducted on risk models after cardiac surgery estimating mortality and morbidity, but to date, there is no consensus regarding the best scoring system after cardiac surgery. 15 Our results showed that the preoperative score (EuroSCORE) underestimated the mortality risk in our patient population.…”
Section: Discussionmentioning
confidence: 99%